Pelayanan Kesehatan Reproduksi Remaja : Sistematik Review - Aima, Syahrifah; Erwandi, Dadan (Universitas Pahlawan Tuanku Tambusai, 2024)
Indonesian National Population and Family Planning Board defines youth as unmarried individuals aged 10-24 years. Globally, every year there are more than 1,2 million adolescent deaths due to preventable or treatable health problems and that were occurred due to lack of adequate information or limited access to health services. The purpose of this review to conclude and explore related to adolescent reproductive health services. This research is a systematic review using the search engines Pubmed, Science Direct and Google Scholar. Search result through search engines found as many as a 5 relevant articles and analyzed them. This review found two themes: the determinants of adolescent reproductive health services, including knowledge, perceptions, and needs; and barriers to adolescent reproductive health services, including facilities, costs, staff, lack of privacy and confidentiality, social culture and policies.